2019
DOI: 10.1080/02656736.2019.1629650
|View full text |Cite
|
Sign up to set email alerts
|

A planning strategy for combined motion-assisted/gated MR guided focused ultrasound treatment of the pancreas

Abstract: Objective: To develop and evaluate a combined motion-assisted/gated MRHIFU heating strategy designed to accelerate the treatment procedure by reducing the required number of sonications to ablate a target volume in the pancreas. Methods: A planning method for combined motion-assisted/gated MRHIFU using 4D-MRI and motion characterization is introduced. Six healthy volunteers underwent 4D-MRI for target motion characterization on a 3.0-T clinical scanner. Using displacement patterns, simulations were performed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…To improve the safety and efficacy of HIFU treatments, methods of compensating for respiratory motion and improving thermometry have been developed, e.g., by fluidfilling the digestive tract surrounding the pancreas of patients [166][167][168][169][170]. For example, simulation data in seven patients showed that the air in the digestive tract and its proximity to the pancreas led to errors in temperature of more than 10 • C due to differences in the magnetic susceptibility between the two tissues and peristaltic motion.…”
Section: Complications Of Hifu Treatments In Pancreatic Cancer Patientsmentioning
confidence: 99%
“…To improve the safety and efficacy of HIFU treatments, methods of compensating for respiratory motion and improving thermometry have been developed, e.g., by fluidfilling the digestive tract surrounding the pancreas of patients [166][167][168][169][170]. For example, simulation data in seven patients showed that the air in the digestive tract and its proximity to the pancreas led to errors in temperature of more than 10 • C due to differences in the magnetic susceptibility between the two tissues and peristaltic motion.…”
Section: Complications Of Hifu Treatments In Pancreatic Cancer Patientsmentioning
confidence: 99%
“…Abdominal organ motion causes significant errors in magnetic resonance (MR) imaging (MRI) when applied to MR-guided therapies of abdominal or pelvic organs due to organ shift and deformation. 1,2 MR-guidedfocused ultrasound (MRgFUS) therapy performs noninvasive heat delivery under MR supervision that can provide for accurate targeting and noninvasive temperature measurement for therapy control and verification.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In addition, the efficiency of localizing ultrasound energy to the target is reduced due to the target zone moving away from the focus position, necessitating gating or more diffuse treatment zones. 2 As respiration is the main source of abdominal organ motion, compensation techniques for respiratory motion have been proposed and developed to reduce temperature errors in MR thermometry. Most of these studies have designed and used a custom-made respiratory motion phantom to validate their technology.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Clinical development has been enabled by integration of magnetic resonance imaging giving guidance to high-intensity focused ultrasound imaging (MR-HIFU), which has shown promising results for pain palliation. [2][3][4] The MR-HIFU technology is currently being used for palliative treatment of bone metastases, as a second-line treatment after unsuccessful radiation therapy and is occasionally used for tumor control. 5 MR-HIFU provides real-time temperature mapping, enabling the visualization of the thermal dose within the targeted tissue and giving a clear indication of the tissue damage.…”
Section: Introductionmentioning
confidence: 99%